Communications Server for z/OS V1R8 TCP/IP implementation. - White, Bill (Telecommunications engineer); Miyamoto, Yukihiko; Oliveira, Gilson Cesar de; Peschke, Roland (IBM Redbooks, 2006)
This Communications Server (CS) for z/OS TCP/IP Implementation series provides easy-to-understand step-by-step how-to guidance on enabling the most commonly used and important functions of CS for z/OS TCP/IP. In this IBM Redbooks publication we begin by providing an introduction to CS for z/OS TCP/IP. We then discuss the System Resolver showing the implementation of global and local settings for single and multi-stack environments. We then present implementation scenarios for TCP/IP Base functions, Connectivity, Routing, and IPv6 support. Finally, we discuss the Sysplex subplexing available with z/OS V1R8.0 Communications Server.